LOCAL GOVERNMENT READINESS IN THE ERA OF SOCIETY 5.0 - Rizki Anugrah Firdaus; Ardhana Januar Mahardhani; Sunarto, Sunarto (International Journal of Social Science, 2023)
This article aims to describe the readiness of the Pacitan Regency Regional Government in facing the Era of Society 5.0. The method used in this paper is a literature review with the steps used in searching for data being selecting a topic, searching for information, determining the focus of the study, collecting data, presenting data, and writing a report. The data sources in this article were obtained from books, scientific articles, news sources, social media, and personal documents. The analytical method used in this research is the meta-synthesis analysis method which is carried out by summarizing the results of previous research which are in accordance with the research theme using narrative techniques after a selection and extraction process has been carried out on the search results. The conclusion in this paper is that local governments are required to move to technology as a basis for the services provided to the community in various activities. Changes must be made by the government even though the readiness of the existing apparatus is not yet completely ready. The existence of the Wadule Pacitan application is an example of the changes that have occurred in government innovation services in supporting e-government in Pacitan Regency.